The Development of the Science of Hadith in Nasaf - Durbek Abidjanovich Rakhimdjanov (Scientific Trends, 2025)
This article provides an in-depth exploration of the historical development of hadith studies in the city of Nasaf and highlights the contributions of prominent scholars who shaped its intellectual tradition between the 8th and 13th centuries. The study focuses especially on the scholarly activities and legacy of Abu Hafs Umar ibn Muhammad an-Nasafi, one of the most influential hadith experts of the region. By examining biographical information preserved in classical sources such as Kitab al-Qand, the article demonstrates how early Nasaf scholars—including Abu Salih Khalaf ibn Tufail, Abu Hamid Zayd ibn Tufail, and Abu Ya‘la Abd al-Mu’min al-Nasafi—established a firm foundation for hadith transmission and teaching. The study further explains how Nasaf emerged as a major center of Islamic learning, attracting students from numerous surrounding regions.
Keywords: Hadith Studies in Nasaf, Abu Hafs an-Nasafi, Islamic Scholarship in Central Asia, Hanafi Jurisprudence and Maturidi Theology, Kitab al-Qand, Historical Development of Hadith Transmission.